Accounting Information System Performance Problems in Regional Drinking Water Companies in Denpasar City - Ernawatiningsih, Ni Putu Lisa; Sunarwijaya, I Ketut; Arista, Putu Diah; Paramitha, Desak Gede Pradnyani; Darmaputri, Ni Wayan Arie (Journal of International Conference Proceedings, 2024)
Accounting information systems (AIS) are performing better as information technology advances. The aim of the written research is test and obtain empirical evidence whether complexity in information technology, support for top management, formalization of system development, user involvement, as well as training and education programs influence the performance of the accounting information system in Regional Drinking Water Companies Denpasar City. The population of this study consisted of all 296 employees. This research used a purposive sampling method by selecting 71 people. Multiple linear regression is an analytical method for testing hypotheses. Research findings show that formalization of system development and user involvement have a positive effect on AIS performance. However, the sophistication of information technology, top management support, and training and education programs have no effect on the performance of accounting information systems. It is hoped that written research can improve the performance of employees using accounting information systems, therefore increasing the performance of information systems in accounting at Regional Drinking Water Companies Denpasar City.